2018
DOI: 10.1155/2018/9064073
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Transfers of CD4+CD25+ Tregs Raise Foxp3 Expression and Alleviate Mouse Enteritis

Abstract: CD4+CD25+Foxp3+ Tregs control the immune response and maintain immune homeostasis. This study examined whether Tregs can affect mouse enteritis and the Foxp3 (Forkhead transcription factor) transcriptional pathway. Mouse CD4+CD25+ Treg cells were labelled using CFSE (5,6-carboxyfluorescein diacetate succinimidyl ester) and transferred to enteritis model mice. The mice were randomly divided into an enteritis group, a Treg-infusion group, a Treg-inhibiting group, and a control group. Histopathology, ELISA, flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Recently, researchers have investigated the possibility of redirecting the Th2 response in favor of the Th1 response, which could reduce the occurrence of atopy [ 18 ]. Modulation of the immune response via the adoptive transfer of sensitized lymphocytes has been described previously [ 13 , 15 , 19 , 20 ]. However, the studies were mainly focused on the observation of the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers have investigated the possibility of redirecting the Th2 response in favor of the Th1 response, which could reduce the occurrence of atopy [ 18 ]. Modulation of the immune response via the adoptive transfer of sensitized lymphocytes has been described previously [ 13 , 15 , 19 , 20 ]. However, the studies were mainly focused on the observation of the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, OVA-specific Treg cells were transferred to naïve mice, resulting in suppression of the anaphylactic response to OVA [ 14 ]. Wang et al [ 15 ] demonstrated that an adoptive transfer of CD4 + CD25 + Tregs reduced the inflammatory response. Therefore, the transfer of specific Tregs may be a beneficial tool in the inhibition of immune response to OVA.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that IL‐2 is essential for the function of Treg cells. IL‐2 and TGF‐β induce the transformation of initial CD4 + T cells into CD4 + CD25 + T cells and express the forkhead transcription cytokine 3 (Foxp3) . Th17 cells are a pro‐inflammatory subpopulation that promotes autoimmune and tissue damage, while Treg cells control the balance between immune activation and tolerance .…”
Section: Introductionmentioning
confidence: 99%
“…Tregs can suppress a variety of immune cells, including B, NK, NKT, CD4+, and CD8+ T cells, as well as monocytes and DCs, leading to their unique role in maintaining immune tolerance in general and controlling unwanted immune responses at various stages of autoimmunity(Bluestone, Trotta et al, 2015;Wang, Zhu, Wang, Yang, & Du, 2018). It has been well established that Tregs transplantation is a promising method in the field of autoimmune diseases.…”
mentioning
confidence: 99%
“…# p < .05 and ## p < .01 compared with the pZP3 group. H & E, hematoxylin and eosin; pZP3, zona pellucida glycoprotein 3 peptide; SD, standard deviation on the potential of Tregs therapies have been conducted in a series of animal models of diseases, including enteritis, GVHD, transplantation, multiple sclerosis (MS), rheumatoid arthritis (RA), T1D, and inflammatory bowel disease, with good results(Brusko, Putnam, 2010;Cooles, Isaacs, & Anderson, 2013;Qizhi & Bluestone, 2013;Wang et al, 2018). However, there are few studies on the treatment of autoimmune POI.…”
mentioning
confidence: 99%